2018
DOI: 10.1002/chem.201804826
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Rigid and Flexible Core Trivalent Sialosides for Influenza Virus Inhibition

Abstract: Herein, the chemical synthesis and binding analysis of functionalizable rigid and flexible core trivalent sialosides bearing oligoethylene glycol (OEG) spacers interacting with spike proteins of influenza A virus (IAV) X31 is described. Although the flexible Tris‐based trivalent sialosides achieved micromolar binding constants, a trivalent binder based on a rigid adamantane core dominated flexible tripodal compounds with micromolar binding and hemagglutination inhibition constants. Simulation studies indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Molecular dynamics (MD) simulations have become a valuable tool in the last decades to study the dynamical properties of biological systems. With the help of these simulations combined with other analysis techniques, it is possible to make statements regarding conformational dynamics, allostery, protein misfolding, and many other relevant biological features. The investigated systems are quite diverse and range from small to larger biomolecules ,, or even complexes consisting of multiple biomolecules and/or ligands. …”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have become a valuable tool in the last decades to study the dynamical properties of biological systems. With the help of these simulations combined with other analysis techniques, it is possible to make statements regarding conformational dynamics, allostery, protein misfolding, and many other relevant biological features. The investigated systems are quite diverse and range from small to larger biomolecules ,, or even complexes consisting of multiple biomolecules and/or ligands. …”
Section: Introductionmentioning
confidence: 99%
“…[56] This finding agreed well with antiviral testing data on rigid and flexible core trivalent sialosides too. [57] Another important design variable has been considering linear versus branched scaffolds. [58] In one promising example, Kwon et al reported the fabrication of a branched polyamidoamine scaffold that mirrored the inter-spacing distance between HA proteins on influenza virus particles and intranasal administration of this scaffold was able to protect mice from lethal influenza virus infection.…”
Section: Sialylated Nanoparticlesmentioning
confidence: 99%
“…[ 56 ] This finding agreed well with antiviral testing data on rigid and flexible core trivalent sialosides too. [ 57 ] Another important design variable has been considering linear versus branched scaffolds. [ 58 ] In one promising example, Kwon et al.…”
Section: Virus Particle Binding Inhibitorsmentioning
confidence: 99%
“…These multivalent inhibitors proved particularly effective for lowering the binding ability of human adenovirus or influenza virus strains, by blocking trimeric sialic acid binding proteins at the surface of the viral capsides. [10][11][12][13][14] The viral neuraminidase, a homotetrameric enzyme allowing virions release from cell surfaces after sialic acid cleavages, was also efficiently inhibited by the same approach. Oligo-and poly-mers of the drug zanamivir (ZV), showed impressive in vivo protection of infected mice, higher than the parent ZV.…”
Section: Introductionmentioning
confidence: 99%
“…Virulence factors interfering with host sialoglycans may also be targeted or inhibited efficiently with synthetic glycoclusters bearing several copies of the sialic acid epitope. These multivalent inhibitors proved particularly effective for lowering the binding ability of human adenovirus or influenza virus strains, by blocking trimeric sialic acid binding proteins at the surface of the viral capsides [10–14] . The viral neuraminidase, a homotetrameric enzyme allowing virions release from cell surfaces after sialic acid cleavages, was also efficiently inhibited by the same approach.…”
Section: Introductionmentioning
confidence: 99%